The Single-Cell Sequencing: A Dazzling Light Shining on the Dark Corner of Cancer - Li, Jing; Yu, Nan; Li, Xin; Cui, Mengna; Guo, Qie (Frontiers in Oncology, 2021)
Tumorigenesis refers to the process of clonal dysplasia due to the collapse of entrenched growth regulation in “selective” cells caused by the action of various carcinogenic factors. It is surely that these “successful” tumor cells pass on the genetic templates to their generations in evolutionary terms, but they also constantly embellish themselves to adapt to ever-changing host environments. In particular, single tumor cell exhibits a unique peculiarity, also known as intratumor heterogeneity(ITH) that is tipped to trigger tumor development, metastasis, chemoresistance and immune escape. Ascertaining ITH is urgently required for the diversity and complexity identification of tumor microenvironment(TME),leaving us a persistent challenge. The single cell sequencing(SCS) furnished a powerful tool to uncover the ITH, by which the distribution of genomic sequence in a single cell was gauged, and the genetic variability among tumor cells was distilled. SCS provided a fundamental perception about assigned diversity in a given surrounding TME,thus improving cancer diagnosis and prognosis prediction, as well as monitoring of therapeutic response. Herein, we will discuss the advances of SCS, and review the progress of SCS application in tumor implication based on the current evidence.